Poem Opposition between Heritage and Modernity (Shawqi and Ibn Zaidoun) as a model - Al-Saedl, Ghassan Abbas Abdulzahra; Al- Behadily, Jabbar Majld Bachay (International Journal of Psychosocial Rehabilitation, 2020)
Andalusian literature is a volcano boiling and hurricane wilder, when we read Ibn Zaydoon early in our lives did not yield in the mind of that belongs to the era involved a lot of bitterness and disappointments of hope as a result of a divorce spiral father m of hand a, because of a conflict between the (Princes of external and precursors). But at the time, which was the knives sedition work in Waller just around the corner, the pens do a civilization in the fields of external years Walt pet and creativity and all levels in thought, science, arts and literature. The face another object of freedom, at that stage allowed the product of the Arab civilization now my tongue to keep flowing upward until reaching the tastiest a wealth! And the emergence of Walt Take the hand of Ibn Zaydoon, Shawki took opposition of his poem Allen and the intention of Walsh, after that shared a in the nature of suffering the ills of time, including superimposed on each other from exile and displacement and weird, to fall both in the experience of love deep and nostalgia sweeping fills its body, to face the then mourn the manifest one, he loved son Zaydoon birth, and I love Shawki Egypt, is not surprising in his position, was to her more longing and nostalgia and love, pumping Meh in the same sense of alienation from his homeland. It is out of this love and its accompanying deprivation, estrangement and longing, each of the poets from Andalusia uttered anger at time, embodying their anger at the idea of separation.